Climate change communication in Singapore - Ho, Shirley S. (Oxford University Press, 2021)
Climate change is not a new topic, but it remains an unsolved issue for most countries in the world. Singapore, a small island nation, is not spared from climate change. The issue is worsened because Singapore is not endowed with natural resources and the country is mainly dependent on imported fossil fuels to generate energy. The burning of fossil fuels releases carbon into the air, intensifying the greenhouse effect. Furthermore, the recurring episodes of haze in Singapore have posed a threat to public health. Realizing the importance of public perceptions on climate change mitigation, the Singapore government and academic researchers have conducted studies to understand public perceptions of climate change. Although the general public do not have great concern about climate change, research suggests that interpersonal communication, information campaigns, and mass communication may have an impact on public awareness of climate change. Attention to mass media, such as newspapers and television, has been found to shape public perception of climate change in Singapore and increase public knowledge of climate change. In addition, the Singapore government has introduced the topic of climate change into the education system to cultivate sustainability among the young generations. Campaigns and programs were funded and organized by the Singapore government as well as the non-governmental organizations to raise the awareness of climate change among Singaporeans. In order to sustain public awareness and concern about climate change, continuous communication strategies are necessary.